Beginning Criminal Law. - Carr, Claudia (Beginning the law., 2013)
Whether you're new to higher education, coming to legal study for the first time or just wondering what Criminal Law is all about, Beginning Criminal Law is the ideal introduction to help you hit the ground running. Starting with the basics and an overview of each topic, it will help you come to terms with the structure, themes and issues of the subject so that you can begin your Criminal Law module with confidence. Adopting a clear and simple approach with legal vocabulary explained in a detailed glossary, Claudia Carr and Maureen Johnson break the subject of criminal law.